Evaluating The Effect of Fair Value Adjustments to Investment Property Based on Profitability Ratios - Anet Smit; Beitske Van der Niet; Martin Botha (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: The aim of the study was to determine whether fair value adjustments to investment property affect the profitability ratios of listed companies. Design/Methodology/Approach: To investigate the problem, a brief literature overview of performance analysis through ratio calculations, as well as fair value measurement are discussed. These discussions are based on the International Financial Reporting Standards (IFRS), IFRS 13 and International Accounting Standards (IAS), IAS 40. IAS 40 addresses how the value of investment property may be recognised through the fair value model. To determine whether the recognition of fair value adjustments affect the profitability ratios of sampled companies, the Wilcoxon rank test and Cohen’s d-value were used as statistical measures to fulfil this objective. The Top 40 companies as listed on the Johannesburg Stock Exchange (JSE) in South Africa were populated, and judgment sampling was applied to calculate the sampling frame.Research findings: The results demonstrate that 50% to 75% of the sampled companies had profitability ratios, which were impacted by the recognition of fair value adjustments. These findings are relevant to potential investors who need to interpret financial ratios to improve investment decisions. Finally, the study recommends that the prospective investor eliminate fair value adjustments when profitability ratios are calculated.Theoretical contribution/Originality: The contribution of the study is that fair value adjustments (favourable or unfavourable) relating to IAS 40 affect the decisions taken by users of the financial statements. Substantial changes to profit or loss and/or investment property significantly impact ratio analysis outcomes and, therefore, investor decision making. The research contributes to the use of fair value adjustments and its impact on profitability ratios. Practitioner/Policy implications: Regulators may benefit from the findings when considering regulatory reforms of accounting practices as well as the disclosures required that assist the users of financial statements.